Final Income Tax on Deposit Interest - Alya Safina Nainggolan; Ratna Septiyanti (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the mechanism for withholding and collecting Income Tax (PPh) Article 4 paragraph (2) on deposit interest at Bank BRI KCP Tanjung Agung. The research method used is descriptive with a qualitative approach. Data collection was carried out through direct interviews with the bank’s management and literature studies. The results of the study indicate that Bank BRI KCP Tanjung Agung has carried out withholding of Income Tax Article 4 paragraph (2) automatically through the banking system (by system) right when the deposit interest is due. The tax calculation applies a final rate of 20% of the customer’s gross interest income. However, there are exceptions to tax withholding for customers with nominal deposits of no more than IDR 7.5 million in accordance with PMK Number 212/PMK.03/2018. Overall, the mechanism for withholding, calculation, and payment of taxes at this bank has been running effectively and complies with applicable tax regulations.